2004
DOI: 10.1002/ar.a.20013
|View full text |Cite
|
Sign up to set email alerts
|

Occurence of lipid bodies in canine type II pneumocytes during hypothermic lung ischemia

Abstract: Type II pneumocytes defend the pulmonary alveolus by synthesis and secretion of surfactant and by contributing to alveolar epithelial regeneration. Lipid bodies are regarded as intracellular domains for the synthesis of eicosanoid mediators that can be induced by inflammatory stimuli. The aim of the present study was to establish whether hypothermic ischemic lung storage without further preservation measures leads to an induction of lipid body formation in canine type II pneumocytes. The lungs of 18 dogs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…Traditionally, lipofibroblasts have been identified histologically by the presence of intracellular lipid droplets, markers of an adipose like phenotype, enzymatic properties, characteristic cytokines, and canonical marker genes like Plin2 , Lpl , and Fgf10 among others ( El Agha, et al., 2014 ; Rehan, et al., 2006 ). The reliance on lipid dyes, and/or associated genes like PLIN2, to distinguish and quantitate lipofibroblasts in the lung is not ideal given that lipid droplets, and associated genes, exist and are expressed by a variety of pulmonary cell types ( Ntokou, et al., 2017 ; Mochizuki, et al., 2011 ; Besnard, et al., 2009 ; Ochs, et al., 2004 ; Zhang and Chawla, 2004 ; Dvorak, et al., 1992 ). More recently, lineage tracing studies have demonstrated Tcf21 to be preferentially expressed in adult murine lung lipofibroblasts while previous reports suggested both Pdgfra + and Fgf10 + lineage lung stromal cell populations included lipofibroblasts ( Park, et al., 2019 ; Al Alam, et al., 2015 ; Barkauskas, et al., 2013 ; Chen, et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, lipofibroblasts have been identified histologically by the presence of intracellular lipid droplets, markers of an adipose like phenotype, enzymatic properties, characteristic cytokines, and canonical marker genes like Plin2 , Lpl , and Fgf10 among others ( El Agha, et al., 2014 ; Rehan, et al., 2006 ). The reliance on lipid dyes, and/or associated genes like PLIN2, to distinguish and quantitate lipofibroblasts in the lung is not ideal given that lipid droplets, and associated genes, exist and are expressed by a variety of pulmonary cell types ( Ntokou, et al., 2017 ; Mochizuki, et al., 2011 ; Besnard, et al., 2009 ; Ochs, et al., 2004 ; Zhang and Chawla, 2004 ; Dvorak, et al., 1992 ). More recently, lineage tracing studies have demonstrated Tcf21 to be preferentially expressed in adult murine lung lipofibroblasts while previous reports suggested both Pdgfra + and Fgf10 + lineage lung stromal cell populations included lipofibroblasts ( Park, et al., 2019 ; Al Alam, et al., 2015 ; Barkauskas, et al., 2013 ; Chen, et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first report of the cholesterol content of a cell type freshly isolated from the ABCA1Ϫ/Ϫ mouse, other than macrophages. One of the striking features of type II cells in intact lungs of ABCA1Ϫ/Ϫ mice was the presence of spherical, nonmembrane-bound cytoplasmic organelles containing amorphous material, typical in appearance to lipid bodies (48). In other cell types, lipid bodies represent a site for cholesteryl ester or lipid storage as is the case for smooth muscle cells (66) and macrophages (13) and may be the case for type II cells.…”
Section: Discussionmentioning
confidence: 99%
“…In other cell types, lipid bodies represent a site for cholesteryl ester or lipid storage as is the case for smooth muscle cells (66) and macrophages (13) and may be the case for type II cells. Few are present in pneumocytes under normal conditions but are induced in response to stress such as ischemia and are felt to be the site of eicosanoid mediator synthesis (48). The role of lipid bodies in the type II cells of the lungs from ABCA1Ϫ/Ϫ mice is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Such organelles can be found regularly in several types of cell and appear to be inducible in nearly all cell types (33) and to be important for the synthesis of eicosanoids (61,62). Under normal conditions, in the alveolar region, they occur frequently in lipofibroblasts and rarely in other cell types, such as alveolar epithelial type II (AE2) cells (8,36). The latter are known to synthesize, store, secrete, and partly recycle pulmonary surfactant (10).…”
mentioning
confidence: 99%